Identification of new binding proteins of focal adhesion kinase using immunoprecipitation and mass spectrometry - Binh Thanh Nguyen; Pyun, Jae-Chul; Lee, Sang-Guk; Kang, Min-Jung (Nature Publishing Group, 2019)
Focal adhesion kinase (FAK) is a 125 kDa protein recruited as a participant in focal adhesion dynamics and serves as a signaling scaffold for the assembly and subsequent maturation of focal contact. Identification of new FAK binding proteins could reveal potential signaling targets and contribute to further development of therapeutic drugs in the treatment of colon cancer. Here, we applied a functional proteomic strategy to identify proteins that interact with FAK in human colon cancer cell line HCT-116. Proteins were targeted by coimmunoprecipitation with an anti-FAK antibody and resolved on 1D-SDS-PAGE. The gel was excised, reduced, alkylated, and trypsin digested. Tryptic peptides were separated by nano-LC-MS/MS by an LTQ-Orbitrap-Velos spectrometer. We identified 101 proteins in the immunocomplex under epithelial growth factor (EGF) stimulation. Three proteins, zyxin, nesprin-1, and desmoplakin, were discovered and validated using reciprocal immunoprecipitation and Western blot analysis. Then, we sought to study the biological relevance of these proteins by siRNA transfection of HCT-116 cells. According to the results, zyxin might play a central role as an upstream regulator to mediate critical cancer-related signaling pathways. Zyxin and nesprin-1 depletion significantly impaired cell migration and invasion capabilities. Additionally, we performed ELISA assays on serum samples from patients with colon cancer instead of cell models to quantify the protein levels of zyxin and nesprin-1. Our results suggested that zyxin and nesprin-1 are not only promising therapeutic targets but also potential diagnostic biomarkers for colon cancer.